Excessive miR-152-3p Results in Increased BAFF Expression in SLE B-Cells by Inhibiting the KLF5 Expression - Luo, Shuangyan; Ding, Shu; Liao, Jieyue; Zhang, Peng; Liu, Yu; Zhao, Min; Lu, Qianjin (Frontiers in Immunology, 2019)
The increased BAFF expression in B-cells of patients with systemic lupus erythematosus (SLE) is associated with B-cell hyperstimulation and T-cell hyperactivity, but the underlying mechanisms are still unclear. This study aimed to uncover the mechanisms that regulate the BAFF expression in SLE B-cells. The results demonstrated that the expression of miR-152-3p was significantly increased in SLE B-cells compared with normal controls. This study confirmed that Kruppel-like factor 5 (KLF5) was a direct target of miR-152-3p, and it could bind to the promoter region of BAFF and inhibit its expression in B-cells. The upregulation of miRNA-152-3p expression decreased the KLF5 expression and increased the BAFF expression in SLE B-cells. Knockdown of miR-152-3p expression inhibited the self-reactivity of SLE B-cells, thereby reducing the autoantibody production. The increased miR-152-3p expression in SLE B-cells led to an increase in BAFF expression by inhibiting KLF5 expression. These factors caused B-cell self-reactivity and autoantibody production, allowing participation in the disease process of SLE.